ROLE OF INFORMATION TECHNOLOGY IN STRENGTHENING WOMEN’S SAFETY IN INDIA: AN ANALYTICAL STUDY - Patil , Harshali; Singh, Anant Manish; Singh, Kinjal Prithviraj; Tiwari, Arya Brijesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Women’s safety remains a pressing concernm with rising incidents of gender-based violence despite advancements in law enforcement. 445,256 crimes against women were reported in 2022 showing a 12.9% rise from 2018. Technology-driven solutions such as mobile safety applications, wearable devices and AI-based surveillance, offer promising interventions. However, gaps persist in public awareness, usability, real-time police integration and trust in these technologies. Existing research lacks comprehensive evaluations of their effectiveness and user concerns. This study examines the adoption, perception and impact of technology-based safety solutions for women, using survey data and testimonials to assess real-world effectiveness. Findings indicate that while awareness of such tools is increasing, concerns over data privacy, reliability and law enforcement responsiveness hinder widespread adoption. Mobile safety apps and wearables emerged as the most trusted solutions, yet respondents emphasized the need for improved emergency response systems and AI-powered predictive safety measures. By addressing these gaps, our research provides data-driven insights into user needs, shaping policy recommendations and technological enhancements. The study underscores the urgent need for seamless integration between technology and law enforcement ensuring real-time intervention and public trust. This study is based on data collected through a structured survey with 265 respondents from diverse demographics across India. The survey assessed awareness, adoption and effectiveness of technology-driven safety solutions for women. These findings have significant implications for policymakers, developers and advocacy groups highlighting the need for safer, more reliable and accessible solutions. As technology evolves, a collaborative approach involving stakeholders, law enforcement and communities is essential to strengthen women’s safety. This research bridges the gap by offering an evidence-based perspective on optimizing existing solutions, fostering innovation and advancing a safer, technology-driven future for women.